SCIENTOMETRIC DIMENSIONS OF INNOVATION COMMUNICATION PRODUCTIVITY OF THE CHEMISTRY DIVISION AT BHABHA ATOMIC RESEARCH CENTRE - Kademani, B. S.; Kumar, Vijai; Surwase, Ganesh; Sagar, Anil; Mohan, Lalit; Gaderao, C. R.; Kumar, Anil; Kalyane, V. L.; Prakasan, E. R. (Malaysian Journal of Library and Information Science, 2005)
Scientrometric analysis of 1733 papers published by the teams comprising total of 926 participating scientists at Chemistry Division of Bhabha Atomic Research Centre (BARC) during 1970-1999 in the domains: Radiation & Photochemistry and Chemical Dynamics (649), Solid State Studies (558), Inorganic, Structural and Materials Chemistry (460) and Theoretical Chemistry (66) were analysed for yearwise productivity, authorship pattern and collaboration. The highest number of publications in a year were 98 and 104 produced in 1989 and 1996 respectively. The average number of publications per year was 57.76. The highest collaboration coefficient 1.0 was in 1977 and 1999. The authors with most prolific publications were J. P. Mittal (204), R. M. Iyer (190), J. V. Yakhmi (156), V. K. Jain (106), Hari Mohan (96), K. N. Rao (92), I. K. Gopalakrishnan (80), P. N. Moorthy (78), T. Mukherjee (77), and S. K. Kulshreshtha (74). The core journals preferred for publishing with high number of publications were: Indian Journal of chemistry - A (96), Radiation Physics and Chemistry (92), Chemical Physics Letters (67), Journal of Physical Chemistry (59) and Indian Journal of Chemistry (45). Publication concentration was 28.57% and publication density was 5.48. Top ranking journals publishing chemistry division BARC publications were from UK (471), India (326), The Netherlands (302), USA (277) and Switzerland (104).